2015
DOI: 10.18632/oncotarget.6048
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the SIN3A-PF1 interaction inhibits epithelial to mesenchymal transition and maintenance of a stem cell phenotype in triple negative breast cancer

Abstract: Triple negative breast cancer (TNBC) is characterized by a poorly differentiated phenotype and limited treatment options. Aberrant epigenetics in this subtype represent a potential therapeutic opportunity, but a better understanding of the mechanisms contributing to the TNBC pathogenesis is required. The SIN3 molecular scaffold performs a critical role in multiple cellular processes, including epigenetic regulation, and has been identified as a potential therapeutic target. Using a competitive peptide correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 69 publications
6
52
0
Order By: Relevance
“…Consistent with this, short term treatments of MDA-MB-231 cells with 31-mer SID peptide [6] increased the expression of RARβ2 by 1.5-fold after 24 h, 8.6-fold after 72 h and 24-fold after 144 h of treatments (Figure 1A). A significant increase in RARβ2 expression was also observed in mouse TNBC cells, 4T1, treated with SID peptide (Supplementary Figure S1).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Consistent with this, short term treatments of MDA-MB-231 cells with 31-mer SID peptide [6] increased the expression of RARβ2 by 1.5-fold after 24 h, 8.6-fold after 72 h and 24-fold after 144 h of treatments (Figure 1A). A significant increase in RARβ2 expression was also observed in mouse TNBC cells, 4T1, treated with SID peptide (Supplementary Figure S1).…”
Section: Resultssupporting
confidence: 75%
“…We have previously reported that the chromatin remodeling protein Sin3A is a potential drug target in TNBC [4, 5]. We have developed peptides and small molecule mimetic inhibitors (SMIs) that block protein-protein interactions between the PAH2 domain of Sin3A and Sin3-interaction domain (SID) containing chromatin-associated factors like MAD1 and PF1 [6, 7]. This interference results in basal to luminal differentiation by epigenetic modulation and transcriptional repression of genes that promote epithelial to mesenchymal transition, invasion and stemness [4, 6, 7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports assessing the biological function of Pf1 point to roles in phosphoinositide signaling (7), nervous system development (8), and the epithelial-to-mesenchymal transition and maintenance of a stem cell phenotype (9). To our knowledge, no comprehensive study elucidating the in vivo function of the Pf1 protein has been conducted so far.…”
Section: (Hdac1) Mrg15 and Pf1mentioning
confidence: 99%
“…Deleting Sin3 (or reducing its level by RNAi) can have a fundamentally different effect on the function of the residual complex in comparison to interfering with only specific protein interactions of Sin3 proteins. Currently, studies directly addressing this issue in the same model system are lacking but can be valuable in addressing the contrasting results and questionable status of Sin3A as tumor suppressor (in Drosophila MEN2 model; Das et al, 2013) or as oncogene (in human TNBC cell models; Bansal et al, 2015).…”
Section: Concluding Remarks: Challenges and Roadblocks In Developing mentioning
confidence: 99%